Inovasi Penilaian Tes Kemampuan Ekspresif Pada Buku Bahasa Arab LP2PPM - Tias, Rianda Ayu Ritnaning; Sihono, Sihono (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This study analyzes the forms of expressive Arabic language competency tests in the Lembaga Pengembangan Pesantren Muhammadiyah (LP2PPM) MTs Arabic language textbook for grade VII. The results of the study show that there are two types of tests, namely (1) subjective speaking skills tests (dialogue pronunciation, picture description, sentence structure changes), and (2) objective writing skills tests (sentence modification, improvement, and creation). The author offers alternative test forms, including audio conversation barcodes, stimulus picture descriptions, interviews, and serial picture comments for speaking skills; as well as variations in spelling and writing picture comments for writing skills. This study is expected to produce a more effective, relevant, and applicable assessment model for students and teachers, while contributing to the development of Arabic language learning at the MTs level in Indonesia.